2006
DOI: 10.1002/ijc.21794
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of 3p genes, LTF, SLC38A3 and DRR1, upon growth of human chromosome 3–mouse fibrosarcoma hybrids in severe combined immunodeficiency mice

Abstract: We have applied a functional test for tumour antagonizing genes based on human chromosome 3 (chr3)–mouse fibrosarcoma A9 MCHs that were studied in vitro and after growth as tumours in severe combined immunodeficiency (SCID) mice. Previously, we reported that 9 out of the 36 SCID‐tumours maintained the transferred chr3 (“chr3+” tumours), but lost the expression of the known human TSG fragile histidine triad gene (FHIT) in contrast to 14 other 3p‐genes examined. Here we report the results of the duplex RT‐PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…In addition, the LTF gene is inactivated by genetic and epigenetic mechanisms in lung cancer (24). Previous studies have also indicated that LTF may have a direct effect on tumor cell growth, as suggested by the fact that LTF and an LTF splice variant are downregulated or absent in certain types of cancer (25)(26)(27)(28). The results of the present study indicate that LTF may also serve as an important tumor suppressor gene in GC.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, the LTF gene is inactivated by genetic and epigenetic mechanisms in lung cancer (24). Previous studies have also indicated that LTF may have a direct effect on tumor cell growth, as suggested by the fact that LTF and an LTF splice variant are downregulated or absent in certain types of cancer (25)(26)(27)(28). The results of the present study indicate that LTF may also serve as an important tumor suppressor gene in GC.…”
Section: Discussionsupporting
confidence: 67%
“…Accordingly TU3A is characterized as a candidate of tumor suppressor gene (TSG) because of its typical expression pattern as a TSG and the fact that introduction of TU3A suppresses tumor cell proliferation and induces apoptosis (2,6,17,18). Similar to TU3A, as a member of FAM107, HITS was shown to be decreased or absent in gastric and colorectal cancers and to inhibit tumor cell proliferative responses to growth factors in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…The deletion in chromosomal 3p21.31 was also reported in different cancers including HNSCC. [28][29][30] Deletions in the D1 and D3 regions overlapped with the deletions in C3CER1 (Common Eliminated Region 1) and 21.3 LUCA (Lung Cancer) reported by Kost-Alimova and Imreh 30 and Senchenko et al, 31 respectively. However, deletion in the D2 region has not been reported earlier.…”
Section: Resultsmentioning
confidence: 75%